2017
DOI: 10.1080/14760584.2018.1406800
|View full text |Cite
|
Sign up to set email alerts
|

The 17D-204 and 17DD yellow fever vaccines: an overview of major similarities and subtle differences

Abstract: The yellow fever vaccine is a live attenuated virus vaccine that is considered one of the most efficient vaccines produced to date. The original 17D strain generated the substrains 17D-204 and 17DD, which are used for the current production of vaccines against yellow fever. The 17D-204 and 17DD substrains present subtle differences in their nucleotide compositions, which can potentially lead to variations in immunogenicity and reactogenicity. We will address the main changes in the immune responses induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
1
15
0
3
Order By: Relevance
“…Currently, the WHO recommends one life-time dose of the YF vaccine; however, this is controversial for two reasons: the level of neutralizing antibodies drops years after vaccination and cases of YF infection have occurred in previously vaccinated individuals [40,[60][61][62][63]. Even though YF vaccine is highly immunogenic and able to induce a robust antibody response and a strong and polyfunctional cellular immune response, recent studies demonstrated the importance of booster doses to ensure a long-term persistence of memory components in response to 17DD YF vaccine [60][61][62]64]. These recent findings suggest that in YF endemic areas, at least an additional dose of the vaccine should be administered after the first immunization, in order to avoid the reduction in neutralizing antibodies titers below the protective levels [60][61][62].…”
Section: Challenges and Lessons Learnedmentioning
confidence: 99%
“…Currently, the WHO recommends one life-time dose of the YF vaccine; however, this is controversial for two reasons: the level of neutralizing antibodies drops years after vaccination and cases of YF infection have occurred in previously vaccinated individuals [40,[60][61][62][63]. Even though YF vaccine is highly immunogenic and able to induce a robust antibody response and a strong and polyfunctional cellular immune response, recent studies demonstrated the importance of booster doses to ensure a long-term persistence of memory components in response to 17DD YF vaccine [60][61][62]64]. These recent findings suggest that in YF endemic areas, at least an additional dose of the vaccine should be administered after the first immunization, in order to avoid the reduction in neutralizing antibodies titers below the protective levels [60][61][62].…”
Section: Challenges and Lessons Learnedmentioning
confidence: 99%
“… 9 , 11 , 12 Both 17D-204 and 17DD sub-strains are regularly used and provide efficient protection against the disease. 13 To simplify, we use the short term “17D” whenever we mean the 17D-204, 17DD, or both vaccines.…”
Section: The Live-attenuated Vaccine Sub-strains 17d-204 and 17ddmentioning
confidence: 99%
“…In Brazil, there are two vaccines available, derived from the same strain, with very similar and comparable response profiles and reactogenicity -YFV 17DD (Bioman-guinhos©) and 17D-204 (Sanofi Pasteur©) [3,6,7,12]. The current Brazilian immunization schedule recommends a single subcutaneous 0.5 ml dose at nine months of age [6] and is contraindicated in some groups, as follows [3,5,13]:…”
Section: Yellow Fever: Disease and Vaccinementioning
confidence: 99%
“…According to the CDC and Advisory Committee on Immunization Practices (ACIP) recommendations, there are no contraindications or precautions for this special group of patients regarding underlying diseases. However, the contraindications should be carefully observed, and consideration given to the precautions for vaccination when patients are receiving immunosuppressive therapy, following the recommendations for immunosuppressed individuals [12,13,19]. Using: Corticosteroid at a dose of ≥20 mg/day (or > 2 mg/kg/day for patients weighing < 10 kg) prednisone or equivalent, for a period ≥14 days Pulsotherapy with methylprednisolone Immunosuppressants as mycophenolate mofetil or sodic, cyclosporine, cyclophosphamide, tacrolimus, azathioprine JAK inhibitors, such as tofacitinib b b-DMARD bDMARD: biologic disease modifying anti-rheumatic drugs; As the dosage of serum level of leflunomide is difficult and the studies on the risk of vaccinating individuals taking leflunomide at the usual doses are lacked, in cases requiring vaccination, a drug elimination regimen of 8 g of cholestyramine 3 times/day for 11 days or 50 g of activated charcoal 4 times/day for 11 days must be prescribed (similar to Sanofi Pasteur Laboratory recommendation when a woman taking leflunomide become pregnant).…”
Section: Sae In Altered Immune Status Patientsmentioning
confidence: 99%